Cost and return analysis of jowar crop in Bundelkhand region of Uttar Pradesh - Pushpendra, K; Anil, Kumar; Shukla, A N; Manish, K; Avinash, P; deep, N Y; Anurooddha, P S Y; Saurabh, SB (Plant Science Today, 2026)
The current study examines the land distribution pattern, cultivation costs and profitability of jowar crop growers across various farm-size groups. A total of 180 households that grow jowar were surveyed and divided into: marginal [69], small [47], medium [43] and large [21] farms. According to the where cultivation of jowar is being done land distribution, there were 412 hectares (ha) of total land, with an average land holding of 2.29 ha. There was significant variation in land holding among jowar cultivators in the study area, ranging from 0.78 ha in marginal farms to 6.74 ha in large farms. The per-hectare cost rises with farm size, from ₹25138.98 for marginal farms to ₹27323.78 for large farms, with an average cost of cultivation (CoC) was ₹25655.37. According to CoC analysis, particularly on marginal farms where family labor utilization was highest (17.40 %), human labor formed a significant cost component. The cost structure shows that medium and large farms invest more on hiring labor and fixed capital, marginal and small farmers rely more on families for labor. As farm size grows, profitability analysis shows a tendency of diminishing net income. Large farms had the lowest net revenue (₹29240.22/ha), while marginal farms had the highest (₹35721.02/ha). Similar trends were seen in the input-output ratio, which was lowest for large farms (3.78) and greatest for marginal farms (5.24 on Cost A1). Additionally, the benefit-cost ratio decreases from 1.42 for marginal farms to 1.07 for large farms.